EDUCATIONAL POTENTIAL OF NATIONAL TRADITIONS AND CUSTOMS IN THE DEVELOPMENT OF THE STUDENT'S PERSONALITY - Ponsotova Feruza Uktamovna (Innovate Conferences, 2025)
This article analyzes the educational opportunities of national traditions and traditions in comprehensively maturing the student's personality. On the basis of national values, the issues of moral qualities, social activity, patriotism and the development of the perception of the national self are covered in students. Also, ways of effective use of national traditions and Customs in the process of higher education and pedagogical methods are recommended.
Keywords: national tradition, tradition, student personality, upbringing, spiritual development, values, higher education.